Riga, Latvia Sabbatical Leave. - Frank, Ellen J. (2003)
Keywords: dept.mgt; faculty_collection; sabbatical_report

Leadership theory and practice: a “case” in point - Armandi, Barry; Oppedisano, Jeannette; Sherman, Herbert (Management Decision, 2003)
Leadership theory has little value if it cannot be applied to real world situations. A summary review of the literature on leadership theory is provided here first. A disguised real case concerning Ted Shade, a Vice-President at Galactic Chips, Inc. is then provided which describes a manager who is extremely task-oriented. The case analysis follows. It includes questions and answers which connect leadership theory to case specifics and requires learners to analyze the case using differing leadership models. © 2003, MCB UP Limited
Keywords: Leaders; Leadership; Management styles; Psychology; dept.mgt